Endosomal trafficking pathway regulated by ARA6, a RAB5 GTPase unique to plants - Ebine, Kazuo (Landes Bioscience, 2012)
Lineage-specific expansion, followed by functional diversification of key components that act in membrane trafficking, is thought to contribute to lineage-specific diversification of organelles and membrane trafficking pathways. Indeed, recent comparative genomic studies have indicated that specific expansion of RAB and SNARE molecules occurred independently in various eukaryotic lineages over evolutionary history. However, experimental verification of this notion is difficult, because detailed functional analyses of RAB and SNARE proteins uniquely acquired by specific lineages are essential to understanding how new membrane trafficking pathways may have evolved. Recently, we found that a plant-specific RAB GTPase, ARA6, and a plant-unique R-SNARE, VAMP727, mediate a trafficking pathway from endosomes to the plasma membrane in Arabidopsis thaliana. Although a similar endosomal trafficking pathway was also reported in animals, the molecular machineries acting in these trafficking systems differ between animals and plants. Thus, trafficking pathways from endosomes to the plasma membrane appear to have been acquired independently in animal and plant systems. We further demonstrated that the ARA6-mediated trafficking pathway is required for the proper salt-stress response of A. thaliana. These results indicate that acquisition of a new membrane trafficking pathway may be associated with maximization of the fitness of each organism in a lineage-specific manner.